The village - Shyamalan, M. Night; Howard, Bryce Dallas, 1981-; Phoenix, Joaquin; Brody, Adrien; Hurt, William; Weaver, Sigourney, 1949-; Deakins, Roger A., 1949-; Howard, James Newton; Touchstone Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) ([United States] : Touchstone Home Entertainment ; Burbank, CA : Distributed by Buena Vista Home Entertainment, 2005)
In a quiet, isolated village in olde Pennsylvania, there lies a pact between the people of the village and the creatures who reside in the surrounding woods. The townspeople do not enter the woods, and the creatures do not enter the village. The pact stays intact for many years, until the headstrong Lucius Hunt seeks medical supplies from neighboring towns beyond the woods.
Title from container.
Originally released as a motion picture in 2004.
Special features: deleted scenes introduced by the director M. Night Shyamalan; deconstructing 'The village': the making-of the movie; M. Night home movie; production photo gallery.
Director of photography, Roger Deakins ; art directors, Tim Beach, Michael Manson, Chris Shriver ; editor, Christopher Tellefsen ; music, James Newton Howard ; costume designer, Ann Roth ; production designer, Tom Foden ; visual effects supervisor, Syd Dutton ; special effects supervisor, Steve Cremin.
Bryce Dallas Howard, Joaquin Phoenix, Adrien Brody, William Hurt, Sigourney Weaver, Brendan Gleeson, Cherry Jones, Celia Weston, John Christopher Jones.
MPAA rating: PG-13; for a scene of violence and frightening situations.
Keywords: Villages -- Pennsylvania -- Drama; Covenants -- Pennsylvania -- Drama; Demonology -- Pennsylvania -- Drama; Films for the hearing impaired; Feature films; Thriller -- Feature